Prevalence of Cyberbullying Perpetration and Cyberbullying Victimization among Nursing Students in Jordan - Fida'a Eid Al-shatnawi; Amal Mohammad Taisir Ababneh; Fatma Mahmoud Elemary; Ahmad Rayan; Manal Hassan Baqeas (SAGE Publishing, 2024)
Introduction Cyberbullying is a form of bullying or harassment carried out online with the intent to harm others mainly using social media sites. Objective To investigate cyberbullying prevalence and associated factors among nursing students in Jordan. Methods A descriptive, cross-sectional study was conducted. A convenience sample of 428 Jordanian nursing students from three private Jordanian universities was involved in the study. Data were collected in 2022 using the sociodemographic characteristics sheet, cyberbullying perpetration (CBP) scale; and cyberbullying victimization (CBV) scale. Multiple linear regression analysis was performed to identify variables associated with the CBP and CBV scores. Results About 30.1% of the students were not involved in any cyberbullying, while 8.6% were categorized as cyberbullying perpetrators only, 20.4% as victims only, and 40.9% were categorized as cyberbullying perpetrators and victims at the same time. Visual /sexual perpetration and verbal/written victimization were the most prevalent forms of cyberbullying among the studied nursing students. Increasing age was associated with a decreased CBP ( P  < 0.05) and CBV ( P  < 0.01), while male gender was associated with increased cyberbullying perpetration ( P  < 0.01). Conclusions The prevalence of cyberbullying among nursing students in the current study was alarming. The study showed that age was negatively associated with CBP and CBV while being male was associated with increased CBP. Future research may want to consider using a longitudinal research design with more testing variables and a more comprehensive examination of potential causes and impacts of cyberbullying in nursing students. The development of specific policies to combat cyberbullying among Jordanian nursing students is also recommended.